2013
DOI: 10.3917/rsi.115.0008
|View full text |Cite
|
Sign up to set email alerts
|

L'enjeu communicationnel dans le système hospitalier

Abstract: Les nouveaux modes de gestion mis en place depuis quelques années dans les institutions hospitalières ont modifié en profondeur l’organisation de ces dernières. Nombreux sont les écrits qui décrivent certaines conséquences sur le domaine de la communication plus spécifiquement. Par cette étude nous avons cherché à comprendre quel était l’impact concret des nouveaux modes de gestion sur la communication au niveau des cadres, mais également des équipes soignantes et ce, en termes de satisfaction et/ou de stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The same authors also reported the main constraint mentioned by the managers they had interviewed: the time constraints that limit, among other things, their presence with the teams they oversee. The impact on time constraints also has been noted in some other studies (Detchessahar, 2011;Habery-Knuessi, Heeb and de Morgan, 2013). For example, Detchessahar noted that managers must devote themselves to other time-consuming tasks, such as administrative tasks, including those related to various management indicators, or various meetings and committees.…”
Section: New Insightsmentioning
confidence: 80%
“…The same authors also reported the main constraint mentioned by the managers they had interviewed: the time constraints that limit, among other things, their presence with the teams they oversee. The impact on time constraints also has been noted in some other studies (Detchessahar, 2011;Habery-Knuessi, Heeb and de Morgan, 2013). For example, Detchessahar noted that managers must devote themselves to other time-consuming tasks, such as administrative tasks, including those related to various management indicators, or various meetings and committees.…”
Section: New Insightsmentioning
confidence: 80%
“…According to Haberey-Knuessi, et al, the Panel group (expert jury and participants) meets around a table or in front of the Panel, in order to follow the debate [13]. Whenever there are small differences, they come together to bring peace.…”
Section: Methods Of Resolving Internal Hospital Problemsmentioning
confidence: 99%